Pros and Cons of Learning Style: an Implication for English Language Teachers - Rinekso, Aji Budi (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2021)
Learning style becomes a familiar theory for many English language teachers. With the hypothesis of matching instructions and learning styles resulting in effective learning, many of the English language teachers apply the learning style theory within their teaching practices. However, recent studies found that learning style is a myth since there were flaws that appeared in the learning style instruments and hypothesis. This study presents in-depth discussions about the pros and cons of learning styles. Detailed descriptions about the implication for English language teachers entailed at the end of the discussions. This study concluded that English language teachers may focus on (1) assessing students’ background knowledge and interests, (2) identifying students’ lacks and necessities, (3) provide more engaged teaching media and learning materials, (4) boosting students’ autonomy rather than merely getting involved in the raging debates of learning style.